Improving the patient-centred care of children with life-altering skin conditions using feedback from electronic patient-reported outcome measures: protocol for a hybrid effectiveness-implementation study (PEDS-ePROM). Issue 4 (9th April 2021) - Tyack, Zephanie; Simons, Megan; McPhail, Steven M; Harvey, Gillian; Zappala, Tania; Ware, Robert S; Kimble, Roy M
Abstract : Introduction: Using patient-reported outcome measures (PROMs) with children have been described as 'giving a voice to the child'. Few studies have examined the routine use of these measures as potentially therapeutic interventions. This study aims to investigate: (1) the effectiveness of feedback using graphical displays of information from electronic PROMs (ePROMs) that target health-related quality of life, to improve health outcomes, referrals and treatment satisfaction and (2) the implementation of ePROMs and graphical displays by assessing acceptability, sustainability, cost, fidelity and context of the intervention and study processes. Methods and analysis: A hybrid II effectiveness-implementation study will be conducted from February 2020 with children with life-altering skin conditions attending two outpatient clinics at a specialist paediatric children's hospital. A pragmatic randomised controlled trial and mixed methods process evaluation will be completed. Randomisation will occur at the child participant level. Children or parent proxies completing baseline ePROMs will be randomised to: (1) completion of ePROMs plus graphical displays of ePROM results to treating clinicians in consultations, versus (2) completion of ePROMs without graphical display of ePROM results. The primary outcome of the effectiveness trial will be overall health-related quality of life of children. Secondary outcomes will include other health-related quality of life outcomes (eg, child psychosocial and physical health, parent psychosocial health), referrals and treatment satisfaction. Trial data will be primarily analysed using linear mixed-effects models; and implementation data using inductive thematic analysis of interviews, meeting minutes, observational field notes and study communication mapped to the Consolidated Framework for Implementation Research. Ethics and dissemination: Ethical approval was obtained from Children's Health Queensland Human Research Ethics Committee (HREC/2019/QCHQ/56290), The University of Queensland (2019002233) and Queensland University of Technology (1900000847). Dissemination will occur through stakeholder groups, scientific meetings and peer-reviewed publications. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12620000174987).